2016
DOI: 10.1038/srep35641
|View full text |Cite
|
Sign up to set email alerts
|

NtKRP, a kinesin-12 protein, regulates embryo/seed size and seed germination via involving in cell cycle progression at the G2/M transition

Abstract: Kinesins comprise a superfamily of microtubule-based motor proteins involved in essential processes in plant development, but few kinesins have been functionally identified during seed development. Especially, few kinesins that regulate cell division during embryogenesis have been identified. Here we report the functional characterization of NtKRP, a motor protein of the kinesin-12 family. NtKRP is predominantly expressed in embryos and embryonic roots. NtKRP RNAi lines displayed reductions in cell numbers in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…NtKRP was located in the cytoplasm and NtRPL17 was both in the cytoplasm and nucleus. CDKB1-1 is a nuclear and cytoplasmic protein ( Boruc et al , 2010 ; Tian et al , 2016 ). SPYCE-NtKRP, SPYNE-NtRPL17, co-expression combinations of SPYCE-NtKRP+SPYNE-CDKB1-1 and SPYNE-NtRPL17+the empty vector SPYCE were used as negative controls.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…NtKRP was located in the cytoplasm and NtRPL17 was both in the cytoplasm and nucleus. CDKB1-1 is a nuclear and cytoplasmic protein ( Boruc et al , 2010 ; Tian et al , 2016 ). SPYCE-NtKRP, SPYNE-NtRPL17, co-expression combinations of SPYCE-NtKRP+SPYNE-CDKB1-1 and SPYNE-NtRPL17+the empty vector SPYCE were used as negative controls.…”
Section: Resultsmentioning
confidence: 99%
“…The paraffin blocks were cut into 8 µm thick sections. The reaction results of in situ hybridization signals were detected as a dark purple color by adding the substrates nitroblue tetrazolium/5-bromo-4-chloro-3-indolyl-phosphate (NBT/BCIP) ( Tian et al , 2016 ). The hybridization signals were observed with an OLYMPUS IX71 microscope.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…They play critical roles in the unidirectional transport of vesicles and organelles, cytokinesis, signal transduction, morphogenesis, cell division and cell growth in the plant development [40][41][42][43]. Furthermore, previous researches have revealed that the kinesin family genes also participated in plant reproductive development [29][30][31]44]. Especially, kinesin family genes have been proved to be essential for the regulation of early fruit development in Malus domestica and Cucumis sativus [15,17].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, other kinesin genes have been veri ed to possess different biological functions, including root, stem and leaf various vegetative tissues development genes (e.g., DBS1, BC12/GDD1, AtKINESIN-4A/FRA1) [25][26][27][28]; plus anther, male gametophyte, embryo, endosperm and seed development genes ( e.g., SRS3 and NtKRP) [29][30][31]. These works revealed the critical roles of plant kinesins in many essential processes in plant development, including not only plant vegetative growth but also plant reproductive process.…”
Section: Introductionmentioning
confidence: 99%